Food security and nutrition: The Ethiopian case for action - Kaluski, DN; Ophir, E; Amede, Tilahun (Cambridge University Press, 2002)
Objective: To assess the 1999–2000 food security situation and the food relief programmes in Ethiopia, and evaluate the need for a national food and nutrition policy. Design: A systematic search of data sources from the Ethiopian Disaster Prevention and Preparedness Commission (DPPC), the Ethiopian Central Statistical Authority, the World Food Programme (WFP) and United Nations Children's Fund (UNICEF), the bibliographic database Medline and direct contacts with associations, institutions and people concerned with food security in Ethiopia. Setting: Consultations to WFP Ethiopia. Results: Food availability was severely restricted due to recurrent disasters such as drought, flood, war and a lack of diversity of food items. Food accessibility was limited due to a weak subsistence-agriculture-based economy, depletion of assets, absence of income diversity and a lack of alternative coping mechanisms. Food intake adequacy was rarely achieved due to food shortages, improper diet and poor sanitary conditions. There was a lack of early warning data to monitor food security indicators. Food aid programmes did not meet the requirements for food quantities and composition, and faced major obstacles in logistics and targeting of the vulnerable population. Conclusions: Improvements in food security and the eradication of famine will require investment in sustainable projects. There is an immediate need for better planning and targeting of food aid and a national food security monitoring system. A national food and nutrition policy is recommended, focusing both on relief efforts and on underlying factors contributing to the famine.